Writing workshop: from idea to article – a writing guide for beginners - Andu, Yusrina; Yaacob, Nurul Aityqah; Ahmad, Siti Noor Dina; Jaafar, Zuraida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The Writing Workshop: From Idea to Article – A Writing Guide for Beginners was held on 13 June 2025 via Google Meet, attended by 26 lecturers and students and facilitated by Dr. Nur Izzah Binti Jamil from FSKM UiTM Cawangan Negeri Sembilan, Kampus Rembau. The workshop aimed to raise awareness of academic writing standards, develop effective writing skills, and encourage collaboration among participants. It provided guidance on transforming ideas into publishable academic work, including research structuring, writing techniques, and strategies for identifying suitable publication outlets. The program was well received, with over 92% of participants reporting improved knowledge, confidence, and motivation to engage in academic writing and publishing.